(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This article seeks to use selected sociological theories to accountfor the phenomenon of Violence in sport. Two main theoretical approaches are employed herein: thefunctionalist/structuralist approach and symbolic interactionism. The analysis thatfollows leads to the conclusion that Violence which occurs in sport ispredominantly a consequence of Violence in modern societies. Sport, in turn, isjust a convenient area for violent behaviours to be manifested, which oftenhappens more clearly and conspicuously than in societies